Fishers’ Local Ecological Knowledge (LEK) on Connectivity and Seascape Management - Berkström, Charlotte; Papadopoulos, Myron; Jiddawi, Narriman Saleh; Nordlund, Lina Mtwana (Frontiers in Marine Science, 2019)
In developing countries where data and resources are lacking, the practical relevance of Local Ecological Knowledge (LEK) to expand our understanding of the environment has been highlighted. The potential roles of the LEK varies from direct applications such as gathering environmental information to a more participative involvement of the community in the management of resources they depend on. Fishers’ LEK could therefore be useful in order to obtain information to advance management of coastal fisheries. Many targeted fish species migrate between habitats to feed, spawn or recruit, connecting important habitats within the seascape. LEK could help provide answers to questions related to this connectivity and the identification of fish habitat use and migrations for species and areas where such knowledge is scarce. Here we assess fishers’ LEK on connectivity between multiple habitats within a tropical seascape, investigate the differences in LEK among fisher groups and the coherence between LEK and conventional scientific knowledge (CSK). The study was conducted in Zanzibar, Tanzania, a tropical developing country, in 2017. One hundred and thirty-five semi-structured interviews were conducted in six different locations focusing on fish migrations, and matching photos of fish and habitats. Differences between fisher groups were found, where fishers travelling further, exposed to multiple habitats, and fish with multiple gears had a greater knowledge on connectivity patterns within the seascape than those that fish locally, in single habitats and with just one type of gear. A high degree of overlap in LEK and CSK was found, highlighting the potential benefits of collaboration between scientists and fishers and the use of LEK as complementary information in the management of small-scale fisheries.